2012
DOI: 10.1039/c1ay05415e
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline/polyacrylic acid/multi-walled carbon nanotube modified electrodes for sensing ascorbic acid

Abstract: A multi-walled carbon nanotube composite electrode incorporating Polyaniline (PANI) and Polyacrylic acid (PAA) is presented by diffusing aniline and PAA into Nafion-MWCNTs membranes supported upon a platinum macrodisc electrode. Nafion is found to be an ideal medium for dispersion of MWCNTs and for the formation of a homogeneous composite. The composite has been characterized utilizing SEM, TEM, FT-IR and electrochemical techniques. Electrochemical characterization reveals that the redox activity of the compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 63 publications
2
21
1
Order By: Relevance
“…As shown in Figure 2A the anodic peak potential of AA determined by SWV was + 0.243 V vs. Ag/AgCl when using bare CFMs but, meaningfully, the peak was shifted negatively to À0.044 V in the case of Nafion/SWCNT-modified CFMs, indicating a strong electrocatalytic effect of CNTs. This observation is in agreement with previous works describing the electrocatalytic effect on the AA oxidation of MWCNTs-IL-Gel deposited on glassy carbon electrode [31], of MWCNTs/Nafion modified carbon fiber electrode [21] and of MWCNTs/ Nafion layer over platinum disc electrode on AA oxidation [23]. Noticeably, the electrocatalytic oxidation of DA at CFM/Nafion/SWCNT suffered a less pronounced negative shift than AA.…”
Section: Electrocatalytic Oxidation Of Ascorbate At Modifiedmicroelecsupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in Figure 2A the anodic peak potential of AA determined by SWV was + 0.243 V vs. Ag/AgCl when using bare CFMs but, meaningfully, the peak was shifted negatively to À0.044 V in the case of Nafion/SWCNT-modified CFMs, indicating a strong electrocatalytic effect of CNTs. This observation is in agreement with previous works describing the electrocatalytic effect on the AA oxidation of MWCNTs-IL-Gel deposited on glassy carbon electrode [31], of MWCNTs/Nafion modified carbon fiber electrode [21] and of MWCNTs/ Nafion layer over platinum disc electrode on AA oxidation [23]. Noticeably, the electrocatalytic oxidation of DA at CFM/Nafion/SWCNT suffered a less pronounced negative shift than AA.…”
Section: Electrocatalytic Oxidation Of Ascorbate At Modifiedmicroelecsupporting
confidence: 93%
“…By using MWCNT modified microelectrodes [21] and carbon nanotube fiber microelectrodes [22], DA has been measured in the presence of AA. More recently, a polyaniline/polyacrylic/MWCNT modified Pt macrodisc electrode has been reported for measuring AA in the presence of DA and uric acid [23]. Furthermore, the simultaneous determination of AA, DA and uric acid by using a screen-printed graphene electrode [24] and chitosan-graphene modified electrodes has been reported [25].…”
Section: Introductionmentioning
confidence: 99%
“…4e). [24][25][26][27][28][29][30][31], the prepared MgO nanobelt/PLL/GCE exhibited a wider linear range and a lower detection limit. These results indicated that the present MgO nanobelt/PLL/GCE has the potential to be applied effectively in biological systems.…”
Section: Optical Characterizationmentioning
confidence: 99%
“…Using the same approach, these authors developed a highly sensitive and rapid oxalate biosensor by covalently immobilizing oxalate oxidase enzyme onto an electrodeposited MWCNT-PANI composite via EDC/NHS chemistry. 161 Electropolymerization has also been employed by Tiwari et al 162 for the preparation of a composite electrode incorporating PANI and polyacrylic acid (PAA) deposited on a Naon-MWCNT membrane supported over a Pt electrode. Naon has hydrophobic and hydrophilic regions and can wrap around the hydrophobic nanotube surface, and hence it is found to be an ideal medium for MWCNT dispersion, enabling the formation of a homogeneous composite.…”
Section: 151mentioning
confidence: 99%
“…Many examples demonstrate the use of this approach in the specic electrochemical detection of relevant molecules. [158][159][160][161][162][163][164][165][166][167][168][169] For example, an electrode composed of MWCNTs and poly(3-methylthiophene), P3MT, was developed by Agüí et al…”
Section: 151mentioning
confidence: 99%